Proposals for a Barranco of resistance. Contextualism and real estate boom in a monumental zone of Lima - Sarmiento, Mario (2023)
The present article proposes an architectural analysis of the ranch, the classic typologyfrom the district of Barranco in the city of Lima, Peru, emphasizing in the elements that define the colorful and ornamental facades that characterize the urban landscape of the district’s monumental zone. Aside from this, key buildings from the real state developmentof the district that have managed to adapt and reinterpret this historical language will beacknowledged (all the way from the seventies to the contemporary boom), demonstrating a search for a middle point between the antagonistic concepts: the built heritage andthe real state market.